Knowledge sharing behaviour in Malaysia higher education institutions / Nur Imanina Najwa Ruslie, Nora'ayu Ahmad Uzir and Noor Zaidi Sahid - Ruslie, Nur Imanina Najwa; Ahmad Uzir, Nora'ayu; Sahid, Noor Zaidi (Faculty of Information Management, 2022)
Despite efforts by Malaysian higher education institutions to promote knowledge sharing, only a small number of HEI have been involved in these efforts. Academics will be more effective at their work and more productive if they share their knowledge. Knowledge is important for a university to strengthen its research and teaching activities. Knowledge sharing is vital for any tertiary education institution to strengthen research and teaching activities, however, not all academicians are keen or willing to share their tacit knowledge and experiences. Therefore, the valuable knowledge was not well disseminated and under-utilized as available resources. People believe their expertise is valuable and useful and are reluctant to share it without incentives. Hence, this study is aimed at determining the barrier to knowledge sharing among academicians.